PEMBUATAN GENERATOR MIKRO WINDBELT DENGAN OPTIMASI PARAMETER PITA DAWAI DAN MAGNET - Muhammad Hidayat; Jatmiko Endro Suseno (Youngster Physics Journal, 2016)
ABSTRACTWind energy has the potential to be utilized as a power plant. One of the utilization of wind energy into electrical energy by making Windbelt generator. Then do research to find the value of the voltage on the generator Windbelt optimization by varying the parameters of the ribbon and the magnet, the magnetic variation on this Windbelt generator includes a magnet and a thick diameter magnet, variations among others 10,12,15,18,20 mm diameter while the thickness variation between another 1.5 and 2 mm. Then for the ribbon parameters include length of ribbon and tape width, variations in use for a long ribbon among others 60,80,100 cm whereas the variation for bandwidth among others 15,18,20,25,30 mm. In order to obtain the optimal voltage value then the coils and wind speeds need to be noticed and measured, variations 1000,1500,2000 winding coils used for measuring wind speed at 1,2,3,4 m / s. Having done research found value best optimization of parameter variations - variations of which have been taken to optimsi voltage on the generator Windbelt with a diameter of 18 mm, thick magnet 2 mm, band width 20 mm, length of ribbon 60 cm, the number of windings in 2000, the wind speed of 4 m / s. Generate a voltage value stream optimization for 5 Volt, 146 mA and Power 0.73 mWatt large voltage generated Windbelt generator capable of powering the LED.Keywords: Windbelt, voltage optimization, neodymium magnet, ribbon